2013
DOI: 10.1163/15685381-00002907
|View full text |Cite
|
Sign up to set email alerts
|

Rediscovery of the rare tree frog Hyla inframaculata Boulenger, 1882 (Anura: Hylidae), in Amazonian Brazil with notes on variation and distribution, and its generic allocation

Abstract: Hyla (= Osteocephalu.s) inframaculata was described on the basis of one specimen collected more than 130 years ago in the neighbourhood of Santarém, Para, Brazil. Only in 2001 three new specimens were collected in the Belo Monte area of the Xingu River, Para, and ten more in late 2011 and 2012 in the same area. The distribution of the species seems to be restricted to "terra firme" (= not flooded) and temporarily flooded forest between the Tapajós and Xingu rivers, in a band south of the Amazon River. The new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…With 24 currently recognised species, the genus Osteocephalus represents the most specious genus of the subfamily Lophyohylinae Miranda-Ribeiro, 1926 (Frost, 2019). The increasing attention paid to spiny-backed treefrog systematics and biogeography in the last decade (Moravec et al, 2009; Jungfer, 2010; Ron et al, 2010, 2012; Hoogmoed, 2013; Jungfer et al, 2013, 2016; Moravec et al, 2016) has significantly improved our knowledge on Osteocephalus phylogeny, resulting in nomenclatural and biogeographical corrections, descriptions of new taxa and the definition of new candidate species. Among the presently accepted species, O. vilarsi (Melin, 1941) is known only from its holotype and represents the most enigmatic species of Osteocephalus (Jungfer et al, 2013; Frost, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…With 24 currently recognised species, the genus Osteocephalus represents the most specious genus of the subfamily Lophyohylinae Miranda-Ribeiro, 1926 (Frost, 2019). The increasing attention paid to spiny-backed treefrog systematics and biogeography in the last decade (Moravec et al, 2009; Jungfer, 2010; Ron et al, 2010, 2012; Hoogmoed, 2013; Jungfer et al, 2013, 2016; Moravec et al, 2016) has significantly improved our knowledge on Osteocephalus phylogeny, resulting in nomenclatural and biogeographical corrections, descriptions of new taxa and the definition of new candidate species. Among the presently accepted species, O. vilarsi (Melin, 1941) is known only from its holotype and represents the most enigmatic species of Osteocephalus (Jungfer et al, 2013; Frost, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Jungfer (2010) placed Hyla inframaculata in the genus Osteocephalus, and Hoogmoed (2013) then placed O. inframaculatus (Boulenger, 1882) in Dryaderces; consequently, the genus contains two species-D. inframaculata (Boulenger, 1882) and D. pearsoni (Gaige, 1929)-and a third species is being described (Jungfer et al 2013). Dryaderces occurs on the lower Andean slopes of central Peru to the Bolivian Amazon, and in the area between the Tapajós and Xingu rivers in a band south of the Amazon River in the states of Pará and Mato Grosso in Brazil (Hoogmoed 2013, Frost 2017.…”
mentioning
confidence: 99%
“…Similarly, neither Knispel and Barros (2009) collecting in Altamira, nor Oliveira et al (2013) working west of the Belo Monte area, found D. inframaculata. Hoogmoed (2013) examined seven individuals (3 males, 3 females, and a half-grown specimen) collected in 2001 and 2012 in the area of the hydroelectric plant of Belo Monte, Rio Xingu, Vitória do Xingu in the state of Pará, Brazil. These specimens were compared with the holotype of D. inframaculata (BMNH 1947.2.13.10).…”
mentioning
confidence: 99%
See 2 more Smart Citations